Versatile Bioconjugation Chemistries of ortho-Boronyl Aryl Ketones and Aldehydes - Cambray, Samantha (Acc Chem Res, 2018)
Biocompatible and bioorthogonal conjugation reactions have proven to be powerful tools in biological research and medicine. While the advent of bioorthogonal conjugation chemistries greatly expand our capacity to interrogate specific biomolecules in situ, biocompatible reactions that target endogenous reactive groups have given rise to a number of covalent drugs as well as a battery of powerful research tools. Despite the impressive progress, limitations do exist with the current conjugation chemistries. For example, most known bioorthogonal conjugations suffer from slow reaction rates and imperfect bioorthogonality. On the other hand, covalent drugs often display high toxicity due to off-target labeling and immunogenicity. These limitations demand continued pursuit of conjugation chemistries with optimal characteristics for biological applications. A spate of papers appearing in recent literature report the conjugation chemistries of 2-formyl and 2-acetyl phenylboronic acids (abbreviated as 2-FPBA and 2-APBA, respectively). These simple reactants are found to undergo fast conjugation with various nucleophiles under physiological conditions, showing great promise for biological applications. The versatile reactivity of 2-FPBA and 2-APBA manifests in dynamic conjugation with endogenous nucleophiles as well as conjugation with designer nucleophiles in a bioorthogonal manner. 2-FPBA/APBA conjugates with amines in biomolecules, such as lysine side chains and aminophospholipids, in a highly dynamic manner to give iminoboronates. In contrast to typical imines, iminoboronates enjoy much improved thermodynamic stability, yet are kinetically labile for hydrolysis due to the boronic acid activation of the imine. The dynamic conjugation presents a novel binding mechanism analogous to hydrogen bonding and electrostatic interactions. Implementation of this covalent binding mechanism has yielded reversible covalent probes of prevalent bacterial pathogens. It has also resulted in reversible covalent inhibitors of a therapeutically important protein Mcl-1. Such covalent probes/inhibitors with 2-FPBA/APBA warheads avoid permanent modification of their biological target, potentially able to mitigate off-target labeling and immunogenicity of covalent drugs. The dynamic conjugation of 2-FPBA/APBA has been recently extended to N-terminal cysteines, which can be selectively targeted via formation of a thiazolidino boronate (TzB) complex. The dynamic TzB formation expands the toolbox for site-specific protein labeling and the development of covalent drugs. On the front of bioorthogonal conjugation, 2-FPBA/APBA has been found to conjugate with α-nucleophiles under physiologic conditions with rate constant (k(2)) over 1,000 M(−1)s(−1), which overcomes the slow kinetics problems and rekindles the interest of using the conjugation of α-nucleophiles for biological studies. With fast kinetics being a shared feature, this family of conjugation chemistries gives a remarkable range of product structure depending on the choice of nucleophile. Importantly, both dynamic and irreversible conjugations have been developed, which we believe will enable a wide array of applications in biological research. In this Account, we collectively examine this rapidly expanding family of conjugation reactions, seeking to elucidate the unifying principles that would guide the further development of novel conjugation reactions, as well as their applications in biology.